Effectiveness of Kupferberg Classification-Based Treatment Protocol in Post Operative Management of Allergic Fungal Rhinosinusitis - Chakravarthy.G, Ahil; Senniappan, Shivakumar (Journal of Neonatal Surgery, 2025)
Background: Allergic fungal rhinosinusitis (AFRS) is a chronic condition managed surgically with functional endoscopic sinus surgery (FESS), but effective postoperative care is essential to prevent recurrence. This study evaluates the effectiveness of Kupferberg classification-based management in AFRS postoperative care. Methods: A total of 65 AFRS patients underwent FESS with polypectomy, followed by a Kupferberg classification-guided steroid regimen. Patients were assessed at POD#5, POD#20, and monthly up to 6 months for symptom improvement and recurrence rates. Results: Early improvement was seen at POD 5 and POD 20 (mean scores: 0.47, 0.48), but recurrence reached 50.8% by POD 6th month, correlating with poor compliance and inadequate maintenance therapy. Conclusion: The Kupferberg classification-based protocol aids early symptom control but is insufficient in preventing long-term recurrence. Enhancing adherence strategies through extended steroid tapering and telemedicine follow-ups may improve outcomes.